2009
DOI: 10.1111/j.1468-1331.2008.02372.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of cardiac metaiodobenzylguanidine scintigraphy in Parkinson disease

Abstract: Although diagnostic accuracy of cardiac MIBG scintigram is high, it is limited because of insufficient sensitivity in patients with short duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
60
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 28 publications
4
60
1
2
Order By: Relevance
“…For MIBG scintigraphy, the overall H/M ratio (1.34) of the PD patients in the present study confirms previous results reporting H/M ratios between 1.19 and 1.57 depending on disease duration, PD subtype, and (probably) also on the exact method of quantification such as size, shape, and positioning of ROIs and the use of maximum compared with mean count values (15,28,(37)(38)(39). Nevertheless, in any case considerable overlap exists for the PD-APD differentiation, suggesting also that MIBG scintigraphy alone is not sufficient to distinguish these entities and that low MIBG uptake alone does not necessarily indicate PD (40).…”
Section: Cardiac Mibg Uptakesupporting
confidence: 80%
See 1 more Smart Citation
“…For MIBG scintigraphy, the overall H/M ratio (1.34) of the PD patients in the present study confirms previous results reporting H/M ratios between 1.19 and 1.57 depending on disease duration, PD subtype, and (probably) also on the exact method of quantification such as size, shape, and positioning of ROIs and the use of maximum compared with mean count values (15,28,(37)(38)(39). Nevertheless, in any case considerable overlap exists for the PD-APD differentiation, suggesting also that MIBG scintigraphy alone is not sufficient to distinguish these entities and that low MIBG uptake alone does not necessarily indicate PD (40).…”
Section: Cardiac Mibg Uptakesupporting
confidence: 80%
“…Similarly, scintigraphy with meta-123 I-iodobenzylguanidine (MIBG) has recently attracted interest in this context, because it also may differentiate APD and PD based on displaying pronounced cardiac sympathetic denervation in PD (15).…”
mentioning
confidence: 99%
“…In their study, Kashihara et al found that 123 I-MIBG myocardial uptake was lower in patients with a long history of PD and the duration of the illness was inversely correlated with the H/M ratio (18). Our data suggest that myocardial sympathetic impairment detectable in PD remains with a worsening in the disease course over time (23). However, such a correlation is controversial (24).…”
mentioning
confidence: 81%
“…We chose to examine only individuals who did not use anti-PD drugs. Furthermore, although some authors consider not to exist any influence of the anti-PD drugs on the results of 123 I cMIBG , it was observed that selegiline increases the serum levels of norepinephrine 28 . Likewise, it was conjectured to have levodopa implication in changing the indexes and images concerning this exam 29 .…”
Section: Discussionmentioning
confidence: 99%